An analysis of the science courses offered in Saint Louis University for prospective elementary school teachers - Valdez, Mario Sabado 1947- (1974)
This analyzes the Science courses offered in Saint Louis University for prospective elementary school teachers. In this study, the researcher found out that most of the subject matter areas taught in college were less emphasized; there were no objectives for a certain course; there was no syllabus in one course; the teaching of the methods course was mainly lecture; and the stduents were not exposed to the different processes that are used in laboratory schools.
Thesis (Master of Arts in Teaching (Elementary Science))--University of the Philippines.
Keywords: Science -- Study and teaching -- Philippines; Science -- Teacher training